2006
DOI: 10.1109/tps.2006.883400
|View full text |Cite
|
Sign up to set email alerts
|

Methods for High Resistivity Measurements Related to Spacecraft-Charging

Abstract: A key parameter in modeling differential spacecraft charging is the resistivity of insulating materials. This parameter determines how charge will accumulate and redistribute across the spacecraft, as well as the time scale for charge transport and dissipation. ASTM constant voltage methods are shown to provide inaccurate resistivity measurements for materials with resistivities greater than ~10 17 Ω-cm or with long polarization decay times such as are found in many polymers. These data have been shown to ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…The free electron densities are ∼ 3.38 × 10 −2 C·m −3 and 3.93 × 10 −2 C·m −3 at the initial surface potentials of −1093 and −2056 V at t = 94.5 h, respectively. Then, we can obtain the resistivity of polyimide, which is ∼ 8.08 × 10 16 -9.40 × 10 16 · m. The results are in good agreement with that measured by charge storage decay resistivity test [9], [58] and SPD methods [12], [13]. The resistivity of polyimide shows that it is too high to be measured by the ASTM method [10], [11].…”
Section: B Space Charge Evolution During Spdsupporting
confidence: 71%
See 2 more Smart Citations
“…The free electron densities are ∼ 3.38 × 10 −2 C·m −3 and 3.93 × 10 −2 C·m −3 at the initial surface potentials of −1093 and −2056 V at t = 94.5 h, respectively. Then, we can obtain the resistivity of polyimide, which is ∼ 8.08 × 10 16 -9.40 × 10 16 · m. The results are in good agreement with that measured by charge storage decay resistivity test [9], [58] and SPD methods [12], [13]. The resistivity of polyimide shows that it is too high to be measured by the ASTM method [10], [11].…”
Section: B Space Charge Evolution During Spdsupporting
confidence: 71%
“…Electrons will be injected into and migrate in the upper half energy band [28]. In the meantime, the surface potential will decay in time [9], [11]. The SPD curves can be divided into different parts, which are resulted by different physical processes, respectively.…”
Section: Uct Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This region is fit by Eq. (2), from which a decay time and the dark resistivity of the material may be derived [33]:…”
mentioning
confidence: 99%
“…4,5 In essence and in the case of oxides, it has been shown that breakdown could be delayed by introducing impurities, whose nature and concentrations meet specific requirements, or by achieving a microstructure that favors to some degree the spreading of charges. [6][7][8][9][10][11][12] Indeed, it contributes to the improvement of component reliability of industrial devices, for instance in thin insulating systems as those used in plasma display panels, 13 spacecraft insulating, 14 alumina rf-window, 15 power electronic capacitors, 16 high-k materials of metal-oxidesemiconductor structures, 17 and field emission display spacers. [6][7][8][9][10][11][12] Indeed, it contributes to the improvement of component reliability of industrial devices, for instance in thin insulating systems as those used in plasma display panels, 13 spacecraft insulating, 14 alumina rf-window, 15 power electronic capacitors, 16 high-k materials of metal-oxidesemiconductor structures, 17 and field emission display spacers.…”
Section: Introductionmentioning
confidence: 99%